Influence of bed rest on plasma galanin and adrenomedullin at presyncope. (15th June 2015) - O'Shea, Daniel; Lackner, Helmut K.; Rössler, Andreas; Green, David A.; Gauger, Peter; Mulder, Edwin; Tamma, Grazia; Hinghofer‐Szalkay, Helmut; Valenti, Giovanna; Goswami, Nandu
Abstract Background The role of hormones in reduced orthostatic tolerance following long‐term immobilization remains uncertain. We have previously shown that plasma concentrations of adrenomedullin and galanin, two peptides with vasodepressor properties, rise significantly during orthostatic challenge. We tested the hypothesis that bedrest immobilization increases the rise in adrenomedullin and galanin during orthostatic challenge leading to presyncope. Materials and methods We measured baseline (supine), presyncope and recovery (10 min postpresyncope, supine) levels of adrenomedullin and galanin in 8 healthy men, before and after 21 days of −6° head‐down bed rest (HDBR). Presyncope was elicited using a combined head‐up tilt and graded lower body negative pressure protocol. Orthostatic tolerance was defined as the time taken from the commencement of head‐up tilt to the development of presyncope. Results Orthostatic tolerance time after HDBR reduced by 8·36 ± 5·39 min (P = 0·0032). HDBR increased plasma adrenomedullin concentration to orthostatic challenge (P = 0·0367). Compared to pre‐HDBR, a significant rise in post‐HDBR presyncopal (P < 0·001) and recovery adrenomedullin concentration (P < 0·01) was demonstrated. In contrast, we observed no change in pre‐ and post‐HDBR galanin levels to orthostatic challenge. Conclusions Bedrest immobilization appears to affect adrenomedullin levels in that greater increases in adrenomedullin occur at presyncope following bedrest immobilization. Due to its peripheral vasculature hypotensive effect, the greater levels of adrenomedullin at presyncope following bedrest immobilization may have contributed to the reduced orthostatic capacity postbedrest.